Integrating Basic Sciences into Global Health by Implementing the Translational Research - Shahib, Muhamad Nurhalim; Dhyanawati, Diah; Rofaani, Elrade (International Journal of Integrated Health Sciences, 2013)
An emphasize on herbal medicine in cancer therapy is also included as an example of translational research implementation. A translational research in Faculty of Medicine, Universitas Padjajaran, has been conducted to develop a novel genomic approach (herbal genomic) on herbal crude extracts. This study focuses on the effects of the extracts on specific gene expressions. In this aspect, the concept of molecular targets is slightly different from pharmaceutical approaches  that aim to find compounds that interact with a specific molecule or macromolecule with known function. In this research strategy, the herbal genomic approaches involve screening of herbal extracts that affect particular gene expression related to cell responses rather than a single proteins. The determination of herbal concentration is based on differential gene expression before and after treatment which is analyzed by real time PCR. The results are being compared to the existing small molecule (active molecule) on the gene expressions. All these academic activities require biomedical research workforce to implement the translational research which, in the Faculty of Medicine, Universitas Padjadjaran, is fulfilled by involving the postgraduate students. New crude extract formulation plus specific gene expression profile is a concept required for developing chemotherapeutic agent in Indonesia. Hopefully, this review can support increased cooperation between hospital and academic institutions in implementing translational research in Indonesia.    DOI: 10.15850/ijihs.v1n1.86